2019
DOI: 10.1016/j.omtn.2019.05.002
|View full text |Cite
|
Sign up to set email alerts
|

miR-15a/-16 Inhibit Angiogenesis by Targeting the Tie2 Coding Sequence: Therapeutic Potential of a miR-15a/16 Decoy System in Limb Ischemia

Abstract: MicroRNA-15a (miR-15a) and miR-16, which are transcribed from the miR-15a/miR-16-1 cluster, inhibit post-ischemic angiogenesis. MicroRNA (miRNA) binding to mRNA coding sequences (CDSs) is a newly emerging mechanism of gene expression regulation. We aimed to (1) identify new mediators of the anti-angiogenic action of miR-15a and -16, (2) develop an adenovirus (Ad)-based miR-15a/16 decoy system carrying a luciferase reporter (Luc) to both sense and inhibit miR-15a/16 activity, and (3) inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 72 publications
(105 reference statements)
0
25
0
Order By: Relevance
“…VEGF also affects Tie2 signaling by inducing the release of Ang2 stored in Weibel-Palade bodies (Matsushita et al., 2005) and stimulating the extracellular domain cleavage of Tie2 (Findley et al., 2007). A recent study demonstrated that targeting microRNA-15a and microRNA-16 enhanced Tie2 signaling and improved angiogenesis and perfusion (Besnier et al., 2019), suggesting that the present model can further integrate with computational models of microRNAs to elucidate the intricate interplay between microRNAs, VEGF pathway, and angiopoietin-Tie pathway (Zhao and Popel, 2015, Zhao et al., 2019). The current model provides a platform for further analysis of Tie2 localization and crosstalk with integrin and other signaling pathways to be explored in subsequent studies.…”
Section: Discussionmentioning
confidence: 95%
“…VEGF also affects Tie2 signaling by inducing the release of Ang2 stored in Weibel-Palade bodies (Matsushita et al., 2005) and stimulating the extracellular domain cleavage of Tie2 (Findley et al., 2007). A recent study demonstrated that targeting microRNA-15a and microRNA-16 enhanced Tie2 signaling and improved angiogenesis and perfusion (Besnier et al., 2019), suggesting that the present model can further integrate with computational models of microRNAs to elucidate the intricate interplay between microRNAs, VEGF pathway, and angiopoietin-Tie pathway (Zhao and Popel, 2015, Zhao et al., 2019). The current model provides a platform for further analysis of Tie2 localization and crosstalk with integrin and other signaling pathways to be explored in subsequent studies.…”
Section: Discussionmentioning
confidence: 95%
“…MiR15a has been shown to inhibit angiogenesis. 29,30 We searched and found that rat MALAT1 has a matching site for miR-15a-5p and it is located from 4160 to 4178 bp of rat MALAT1 gene loci. Our study found that HBOinduced exosomes could significantly attenuate the miR15a expression induced by hypoxia in cardiac myocytes ( Figure S6).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies on the diagnostic role of circulating miRNAs in AMI were initially based on big data analysis, but follow-up studies have also confirmed their relationship with cardiovascular disease which we will not discuss it here ( Liu W. L. et al, 2015 ; Wei L. X. et al, 2015 ; Xue et al, 2015 ; He and Huang, 2017 ; Besnier et al, 2019 ; Che et al, 2019 ; Li X. D. et al, 2019 ; Shen et al, 2019 ; Zhang et al, 2019 ). Meder et al (2011) identified two downregulated miRNAs, miR-1291 and miR-663b, among 121 miRNAs related to AMI through whole genome miRNA expression profiling.…”
Section: Circulating Mirnas Function As Diagnostic and Prognostic Biomentioning
confidence: 99%